MELAMPAUI KRISIS: DINAMIKA KINERJA KEUANGAN, INDEKS KEBANGKRUTAN ALTMAN, DAN TRANSFORMASI NILAI PERUSAHAAN - Wicaksono, Christian Edy; Kadarusman, Kadarusman; Maria, Evi (FEB Universitas Sam Ratulangi Manado, 2024)
ABSTRACT This research aims to examine the impact of Financial Performance on Firm Value by incorporating the Bankruptcy Index as a moderating variable. Data were obtained from the financial reports of eight companies in the pulp and paper sector through the Indonesia Stock Exchange website, utilizing purposive sampling. The analysis employed SmartPLS 3 in a quantitative approach. The research findings indicate that Financial Performance has a positive and significant impact on Firm Value, whereas the Bankruptcy Index has a significant negative impact on Firm Value. The Bankruptcy Index, as a moderating variable, does not significantly weaken the influence of Financial Performance on Firm Value. This study contributes to the understanding of the relationship between Financial Performance, Firm Value, and the moderating role of the Bankruptcy Index in the pulp and paper industry. Practical implications support companies in designing more effective financial strategies. Research limitations include the sample size and a focus on a specific industry sector, highlighting the need for further research in diverse industrial contexts for a more comprehensive understanding. Keywords: Financial Performance, Bankruptcy Index, Corporate Value